Pentecostal Paradigms of National Economic Prosperity in Africa - Wariboko, Nimi (Pentecostalism and Prosperity: The Socio-Economics of the Global Charismatic Movement, 2012)
The most existential task facing Africans is economic development. For Christians, this raises the urgent question: what are the African Pentecostal churches’ understandings and teachings on the continent’s economic predicament? This chapter examines aspects of the social teachings of African Pentecostal churches related to national economic prosperity. I have identified five basic theological paradigms that frame the discourse on Africa’s economic development among Pentecostal pastors. These are covenant, spiritualist, leadership, nationalist and developmental.
paid